Knowledge of Anxiety in Midwives in the COVID-19 Pandemic - Nurul Syabin (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2021)
The incidence of COVID-19 cases continues to increase day by day so that health workers as the front line are increasingly under pressure due to the increasing workload, worrying about their health, and their families[1]. One thing that can cause health workers to experience increased anxiety, one of which is the lack of Personal Protective Equipment (PPE) in the workplace[2]. Health workers are at risk of experiencing psychological disorders in treating Covid-19 patients due to feelings of depression, the main cause of which is self-protection which is still less than the needs of health workers[3]. The purpose of this study was to determine the factors that influence the anxiety of midwives during the COVID-19 pandemic at the Bekasi District Hospital in 2021. This study used adesign cross sectional. The population of all midwives in the Bekasi Regency General Hospital is 48 people. The samplingused was techniquepurposive sampling technique by stating several criteria. If it does not meet the inclusion criteria, it is not used. Data analysis using chi square and logistic regression. The results of the statistical test of the knowledge factor with anxiety in midwives during the COVID-19 pandemic using chi square got a value of sig = 0.01. The conclusion of this study is that knowledge has a relationship between knowledge and anxiety in midwives during the COVID-19 pandemic at the Bekasi District Hospital in 2021.